(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Genetic engineering is the in vitro construction of functionally active genetic structures - recombinant DNA, i.e. artificially created genetic programmes. It is a system of experimental techniques that allow to construct in vitro artificial genetic structures in the form of recombinant (hybrid) DNA molecules and transfer the created gene constructs into a living organism, resulting in their incorporation into the genome and active functioning in the organism and its offspring [4,5,6].